Qualitative and Quantitative Methods in Libraries Journal Special Issue: Bibliometrics and Scientometrics - Welsh, Teresa S. (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
Numerous papers and presentations related to bibliometrics have been presented at the International QQML conference each year. This special issue of QQML Journal contains selected papers representing a variety of bibliometric research methodologies.